Eid al-Adha for UMPSA International Students Unique Stories - Jamilah Bebe, Mohamad; Siti Ainun Jariyah, Hassan (UMPSA, 2024)
Hari Raya Haji or Eid al-Adha is one of the biggest festive celebrated by Muslims worldwide, alongside Eid al-Fitr. This celebration occurs annually on the 10th, 11th, 12th, and 13th of Zulhijah. In Malaysia, it was celebrated on 17 June 2024.